A Way of Life: Recovery as a Means of Addressing Substance Use Disorder. Issue 170 (5th January 2021) - Elkins, Becki; Hawkins, Beck; Workman, Christine
Abstract: This chapter explains recovery as an individual process and as an organizing framework for addressing substance use disorders.